Nanobodies dismantle post‐pyroptotic ASC specks and counteract inflammation in vivo - Damien Bertheloot; Carlos WS Wanderley; Ayda H Schneider; Lisa DJ Schiffelers; Jennifer D Wuerth; Jan MP Tödtmann; Salie Maasewerd; Ibrahim Hawwari; Fraser Duthie; Cornelia Rohland; Lucas S Ribeiro; Lea‐Marie Jenster; et al. (EMBO Molecular Medicine, 2022)
Abstract Inflammasomes sense intracellular clues of infection, damage, or metabolic imbalances. Activated inflammasome sensors polymerize the adaptor ASC into micron‐sized “specks” to maximize caspase‐1 activation and the maturation of IL‐1 cytokines. Caspase‐1 also drives pyroptosis, a lytic cell death characterized by leakage of intracellular content to the extracellular space. ASC specks are released among cytosolic content, and accumulate in tissues of patients with chronic inflammation. However, if extracellular ASC specks contribute to disease, or are merely inert remnants of cell death remains unknown. Here, we show that camelid‐derived nanobodies against ASC (VHHASC) target and disassemble post‐pyroptotic inflammasomes, neutralizing their prionoid, and inflammatory functions. Notably, pyroptosis‐driven membrane perforation and exposure of ASC specks to the extracellular environment allowed VHHASC to target inflammasomes while preserving pre‐pyroptotic IL‐1β release, essential to host defense. Systemically administrated mouse‐specific VHHASC attenuated inflammation and clinical gout, and antigen‐induced arthritis disease. Hence, VHHASC neutralized post‐pyroptotic inflammasomes revealing a previously unappreciated role for these complexes in disease. VHHASC are the first biologicals that disassemble pre‐formed inflammasomes while preserving their functions in host defense.